Antagomir-1290 suppresses CD133⁺ cells in non-small cell lung cancer by targeting fyn-related Src family tyrosine kinase - Sun, B; Yang, N; Jiang, Y; Zhang, H; Hou, C; Ji, C; Liu, Y; Zuo, P (Springer Nature, 2015)
Cancer stem-like cells (CSLCs) are involved in cancer initiation, development, and metastasis, and microRNAs (miRNAs) play pivotal roles in regulating CSLCs. miRNA-based therapeutic strategy associated with CSLCs might promise potential new therapeutic approaches. In the present study, we found that miR-1290 was increased in CD133(+) cells. Antagomir-1290 significantly suppressed tumor volume and weight initiated by CD133(+) cells in vivo. Furthermore, antagomir-1290 significantly inhibited the proliferation, clonogenicity, invasion, and migration of CD133(+) cells by targeting fyn-related Src family tyrosine kinase. These findings provide insights into the clinical prospect of miR-1290-based therapies for non-small cell lung cancer.